Authoritative Parenting, Spirituality, and Child Resilience in the Family Environment: A Systematic Literature Review - Preti Ifrigil Firginia; Ichsan Ichsan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Child resilience is an essential adaptive capacity that enables children to cope with developmental challenges, psychosocial stressors, and changing family dynamics. The family environment plays a central role in shaping resilience, particularly through parenting practices and the internalization of spiritual values. This study aimed to systematically examine the role of authoritative parenting and spirituality in the formation of child resilience within the family environment. A systematic literature review was conducted using the PRISMA framework to guide the identification, screening, eligibility assessment, and inclusion of relevant studies. Scholarly articles were retrieved from Google Scholar, Scopus, Crossref, and Garuda/SINTA, and selected based on their relevance to parenting styles, spirituality, child resilience, and family contexts. The selected studies were analyzed through thematic synthesis to identify key patterns, protective factors, and conceptual relationships across the literature. The findings indicate that authoritative parenting and child spirituality function as significant protective factors in strengthening resilience. Authoritative parenting, characterized by warmth, responsiveness, clear boundaries, and open communication, supports children’s emotional security, autonomy, and adaptive coping. Meanwhile, spirituality provides meaning, hope, moral orientation, and inner strength that help children interpret difficulties more constructively. The synthesis further shows that the interaction between warm parenting practices and dialogical internalization of spiritual values produces the most optimal contribution to child resilience. These findings confirm that resilience is not merely an innate trait but develops through a continuous, relational, and holistic process within the family environment. This study highlights the importance of integrating supportive parenting and spiritual value education in family-based interventions, parenting programs, and guidance and counseling practices aimed at strengthening children’s resilience.